Encapsulation by spray drying of crude betacyanins : physicochemical, morphological and nutritional properties of produced powder - Chong, P. H.; Aziz, Mohammad Gulzarul; Yusof, Yus Aniza; Naim, Mohd Nazli; Chin, Nyuk Ling
Amaranth betacyanin, responsible for red or violet colour was extracted from Amaranthus gangeticus by using water extraction method and microencapsulated by spray drying. The physicochemical, morphological and nutritional properties of microencapsulated betacyanins were assessed as influenced by inlet temperature and maltodextrin concentration. The process was conducted on a mini spray dryer and maltodextrin was used as encapsulating agent. Central composite design was used and thirteen experiments were carried out. The responses were betacyanin retention, moisture content, water activity, particle densities, shape, colour values and antioxidant activity. Quadratic effect of both the factors was found positive on betacyanin retention whereas antioxidant was affected by linear change of maltodextrin. Only the effect maltodextrin concentration was found significant on colour value. Particle densities and sizes are slightly affected by the process conditions studied.